Enhancement of ethanol sensing properties by alloying TiO2 with ZnO tetrapods - Santhaveesuk T. (2014)
The TixZn1-xO tetrapods were synthesized using simple thermal oxidation method from Zn and Ti02 mixture. The tetrapods exhibited single crystalline hexagonal wurtzite structure with the prefer growth direction of [0002] along the legs. The sensors based on TixZn 1-x0 tetrapods were fabricated and investigated the ethanol sensing properties. The FE-SEM, HRTEM, SAED, XRD, and RS results suggested that Ti xZn1-x0 alloy was formed with a slightly decrease of c-axis lattice parameter. The decrease of sensor resistance under ethanol atmosphere was observed and suggested that the TixZn1-xO tetrapods possessed n-type property of semiconductor similar to ZnO. The Ti xZn1-xO tetrapod sensors exhibited higher sensitivity than that of pure ZnO tetrapod sensors for entire ethanol concentration with optimum operating temperature of 300 °C. Thus, the enhancement of sensitivity due to alloying TiO2 with the ZnO tetrapods was observed and maybe explained by an increase of adsorbed oxygen ions due to substitution of Ti atom into Zn atom. Also, the slope value of the plot between log(S - 1) and log C suggested that adsorbed oxygen ion species at the surface of the Ti xZn1-xO tetrapods was O2- which was same as pure ZnO tetrapods. Finally, these results have an important implication for a development of ethanol sensors based on metal oxide semiconductors for alcohol breath analyzer. © 2009 IEEE.